Tracking Cairns: Biologging Improves the Use of Seabirds as Sentinels of the Sea - Brisson-Curadeau, Emile; Patterson, Allison; Whelan, Shannon; Lazarus, Thomas; Elliott, Kyle H. (Frontiers in Marine Science, 2017)
In 1987, David Cairns proposed that a gradient of colony-based measures on seabirds could be used to assess food supply in the ocean. Measures closely tied to the ocean, such as foraging trip duration, would be sensitive to small declines in food supply while measures more closely tied with the nest site, such as reproductive success, would be sensitive to large declines in food supply. The continual refinement of tracking devices holds the potential of clearly linking variables measured via seabirds to food supply, possibly extending Cairns' hypothesis. Here, we review the various tests of Cairns' hypothesis, and demonstrate that those tests have had variable success, partly because of the complex and nonlinear relationships between food supply and colony-based measures. We summarise the metrics available from biologgers and argue that such devices can provide a linear indication of food supply that is more sensitive and more easily interpreted. We conclude that Cairns' hypothesis can be extended to biologger-derived parameters and that seabird behaviour can be used as an early warning signal for declining food supply.